General image of tourist destination of Nepal from tourist perspective - Gurung, Amrit Kumar (Journal of Advanced Academic Research, 2015)
Background and objective: Tourists are the people who visit new places to observe the places, natural beauty, cultural-environment, and many more rituals. The study was conducted to explore the general image of tourist destination of Nepal from the tourist perspective. Methodology: The study was conducted in the tourist destination of Kathmandu valley when tourists of different countries were randomly selected. The study was based on the descriptive research design. Structured questionnaires were developed using Likert’s scale. Result: There was no significant association found between the perceptions of tourists in tourist destination of Nepal. Around 38% had neutral answer about the availability of tourist police in tourist destination as well as more than 45% had neutral answer about the effectiveness of tourist police in promoting safe tourism. Conclusion: Natural beauty of tourist destination should be safe and the environment should be cleaned. There is a necessity to increase the numbers of tourist police for the promotion of safe tourism. Journal of Advanced Academic Research Vol.1(1) 2014: 58-67